From White Nation to White Caution: Non-Indigenous Reflections on Indigenous Difference. Issue 3 (3rd July 2019) - Rowse, Tim; Pertierra, Anna Cristina
ABSTRACT: Based on interviews with 31 non-Indigenous Australians during 2015–2017, this article argues that there is no "typical" non-Indigenous Australian way of talking and thinking about Indigenous Australia. Rather, a more plausible reading of our data is that non-Indigenous Australians are experiencing, in a self-aware and cautious way, the ascendancy of the idea that the Indigenous/non-Indigenous distinction is culturally, morally and politically significant. While interviewees varied in their views about Indigenous difference, their awareness that Indigeneity poses relatively new and compelling questions for Australians was evident in their reflexive ways of talking, as they took up a position in (what they evoked or implied as) a field of non-Indigenous opinion. We propose a model of the orthodoxy that defines this field. Reviewing previous research on non-Indigenous Australians' everyday attitudes and opinions about Indigenous Australians, we seek to replace accounts that postulate non-Indigenous thinking as a singular edifice. We present popular discourse as the self-aware taking of positions, in known or imagined fields of opinion.